2021
DOI: 10.1038/s41467-020-20440-5
|View full text |Cite
|
Sign up to set email alerts
|

A logical network-based drug-screening platform for Alzheimer’s disease representing pathological features of human brain organoids

Abstract: Developing effective drugs for Alzheimer’s disease (AD), the most common cause of dementia, has been difficult because of complicated pathogenesis. Here, we report an efficient, network-based drug-screening platform developed by integrating mathematical modeling and the pathological features of AD with human iPSC-derived cerebral organoids (iCOs), including CRISPR-Cas9-edited isogenic lines. We use 1300 organoids from 11 participants to build a high-content screening (HCS) system and test blood–brain barrier-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 80 publications
(49 reference statements)
0
124
0
Order By: Relevance
“…Most recently, Park et al have developed a network-based drug-screening platform by integrating mathematical modeling and hPDBOs with the AD pathological features. Using this platform, they have identified several FDA-approved drugs as candidates for curing AD [ 103 ]. Taken together, these studies have demonstrated that hPDBOs indeed represent a more ideal and efficient model for AD modeling and drug screening.…”
Section: Bos For Modeling Neurodegenerative Disordersmentioning
confidence: 99%
“…Most recently, Park et al have developed a network-based drug-screening platform by integrating mathematical modeling and hPDBOs with the AD pathological features. Using this platform, they have identified several FDA-approved drugs as candidates for curing AD [ 103 ]. Taken together, these studies have demonstrated that hPDBOs indeed represent a more ideal and efficient model for AD modeling and drug screening.…”
Section: Bos For Modeling Neurodegenerative Disordersmentioning
confidence: 99%
“…In addition to studying toxic Aβ species, 3D culture models such as 3D cerebral organoids have been used to test if specific antibodies can block tau pathology [ 50 , 95 , 110 , 111 , 112 ]. Determination of the efficacy and optimal dosage of small molecule drug candidates can also be performed using hiPSC-based AD models.…”
Section: Disease Modeling Using Hipscsmentioning
confidence: 99%
“…Lancaster et al generated cerebral organoids from iPSCs derived from a patient with microcephaly and demonstrated premature neuronal differentiation, which resembled the disease phenotypes [ 15 ]. Moreover, cerebral organoids have been applied for the disease modeling of many central nervous disorders, including Alzheimer’s disease [ 55 , 56 , 57 , 58 , 59 ], frontotemporal dementia [ 60 ], Huntington’s disease [ 61 ], and Parkinson’s disease [ 62 , 63 ]. We previously established a disease model of congenital hypopituitarism with OTX2 mutation using patient-derived iPSCs.…”
Section: Hpsc-derived Organoidsmentioning
confidence: 99%